Growth performance, haematological parameters, antioxidant status and salinity stress tolerance of juvenile Pacific white shrimp (Litopenaeus vannamei) fed different levels of dietary myo‐inositol. (17th April 2018) - Chen, S.J.; Guo, Y.C.; Espe, M.; Yang, F.; Fang, W.P.; Wan, M.G.; Niu, J.; Liu, Y.J.; Tian, L.X.
Abstract: A 10‐week growth trial was run to evaluate effects of myo ‐inositol (MI) on growth performance, haematological parameters, antioxidative capacity and salinity stress tolerance of Litopenaeus vannamei . Six practical diets supplemented with graded levels of MI (designated as MI0, MI600, MI1200, MI2400, MI 3600 and MI4800 for 448.8, 974.2, 1568.0, 2810.6, 3835.5 and 4893.6 mg/kg diet, respectively) were fed to six replicate groups of L. vannamei (mean initial body weight 0.63 ± 0.00 g). The results showed that significant increment of growth performance was observed in shrimp fed MI600 diet than those fed MI1200 diet. Lipid concentration in whole body of the shrimp fed MI600 diet was significantly increased. Shrimp fed MI0 diet had lower total protein (TP) as compared to shrimp fed the MI‐supplemented diets (except MI4800 diet). In general, lower activities of antioxidant enzymes and higher malondialdehyde (MDA) content in haemolymph and hepatopancreas were recorded in shrimp fed MI0 diet, compared to those fed the MI‐supplemented diets. Reduced survival after 7‐h salinity stress was present in shrimp fed MI0 diet as compared to those fed MI4800 diet. Dietary MI requirement for glutathione peroxidase activity of L. vannamei was 2705 mg/kg diet.